Means to Increase Texts Accessibility for Primary Schoolers with ASD during Teaching Process - O.V. Zagumennaya; P.L. Bogorad (Moscow State University of Psychology and Education, 2023)
Children with autism spectrum disorder (ASD) are often limited in understanding spoken and written language. To make texts accessible for children with ASD specialists use means that improve understanding of verbal or written information and make learning process more successful. The article discusses why children with ASD have difficulties in precepting and understanding textual information, for example, poor vocabulary, ignorance of words lexical meaning, misunderstanding of figurative language or hidden meaning behind words due to poor social experience. We present the main working areas to develop and improve speech understanding: improving reading skills, developing the ability to listen to an interlocutor, developing phrasal speech, forming initial grammatical representations, etc. The main text types that children encounter in the classroom are also listed, for example, instructions, rules, tasks, literary works. We also offer tools that facilitate working with texts, make them more accessible, and adapt to individual capabilities of students. We give practical recommendations that will be useful both to teachers working with students with ASD and their parents.